Efektifitas Pemungutan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan Di Kabupaten Mojokerto - Nur Ainiyah; Agoes Hadi Poernomo (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This Research is motivated to conduct development research in order to find out the effectiveness of land and building tax collection before the pandemic and during a pandemic. This research uses a qualitative research paradigm. The qualitative research paradigm is usually associated with qualitative research that is descriptive analytical, comparative in nature, focuses on meaning, and data where the data can be obtained by observing and/or document analysis. The research approach used is phenomenology by collecting data using interviews and Documents related to land and building tax. The results of this study indicate that land and building tax payments in Mojokerto Regency can be made online or offline. Land and building tax collection in Mojokerto Regency is collected directly by officials from the Mojokerto Regency regional revenue agency and to this day still involves village government officials. During the period before the pandemic, the effectiveness of land and building tax collection in Mojokerto Regency was in the criteria of being quite effective (2018 and 2019) while during the pandemic it was less effective (2020-2022). This was due to changes in the achievement targets which were also accompanied by a decrease in the realization of land and building tax revenues.